2014
DOI: 10.1890/13-0212.1
|View full text |Cite
|
Sign up to set email alerts
|

Soil mercury and its response to atmospheric mercury deposition across the northeastern United States

Abstract: Abstract. Terrestrial soil is a large reservoir of atmospherically deposited mercury (Hg). However, few studies have evaluated the accumulation of Hg in terrestrial ecosystems in the northeastern United States, a region which is sensitive to atmospheric Hg deposition. We characterized Hg and organic matter in soil profiles from 139 sampling sites for five subregions across the northeastern United States and estimated atmospheric Hg deposition to these sites by combining numerical modeling with experimental dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 59 publications
5
43
1
Order By: Relevance
“…Dry deposition was not included due to a lack of nationally available high‐resolution data. Dry deposition may exceed wet deposition in some regions [ Schroeder and Munthe , ; Sakata et al ., ; Graydon et al ., ; Risch et al ., ; Yu et al ., ] and could potentially be a significant factor affecting Hg availability in such settings. However, when modeled dry deposition was included for five of the sites, Riscassi and Scanlon [] found that the Hg D :DOC ratio actually declined as total deposition increased.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Dry deposition was not included due to a lack of nationally available high‐resolution data. Dry deposition may exceed wet deposition in some regions [ Schroeder and Munthe , ; Sakata et al ., ; Graydon et al ., ; Risch et al ., ; Yu et al ., ] and could potentially be a significant factor affecting Hg availability in such settings. However, when modeled dry deposition was included for five of the sites, Riscassi and Scanlon [] found that the Hg D :DOC ratio actually declined as total deposition increased.…”
Section: Discussionmentioning
confidence: 99%
“…It does not appear that recent wet deposition controls the spatial variability of the stream Hg D :DOC ratio between sites, but it is important to note that MDN data does not reflect historical atmospheric Hg loading to the soil. Previous studies have reported a disconnect between recent atmospheric Hg deposition and Hg in streams [ Hintelmann et al ., ; Brigham et al ., ; Oswald et al ., ], lakes [ Harris et al ., ], and soils [ Obrist et al ., ; Yu et al ., ]. This suggests a time lag between the deposition of Hg to terrestrial watersheds and its transport to streams or a possible loss of Hg during transport (e.g., volatilization).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Obrist et al (2011) hypothesized that this relationship is likely due to differences from centuries of Hg inputs known as "legacy" Hg. However, because the Adirondacks is a region with relatively uniform soil age, disturbance history, and Hg deposition history, it would appear that decomposition processes and nutrient status may be regulating this pattern, and Hg enrichment within the forest floor profile seems to be driven more by ecosystem processes than by historic deposition patterns (Yu et al, 2014).…”
Section: Relationships Between Carbon Nitrogen and Mercury Cyclingmentioning
confidence: 99%